FEMINISME DALAM FILM MARLINA SI PEMBUNUH DALAM EMPAT BABAK - Febryani, Irma (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2018)
The Film tittled Marlina The Murderer In Four Act present a high powered female character named Marlina. The Robber start to loading up her catle and plan to rape her. Marlina defended her self by killing the robbers. Feminist impression deeply felt on Marlina. She does not obey on the command of the man and take the fight. Marlina made a long journey by herself for a justice, although the struggle is futile. With the some of references, the author analyzes all action of feminism conducted by marlina chacacter, also analyzes the action that contain the elements of patriarchy which men do to the women. With this research, will be delivered the things are done by marlina to fight for his right with all the courage. There is a message to be delivered by the film creator through the character of marlina, that is for women to be braveand not shackled by patriarchal culture.